Effects of Altered Levels of Pro- and Anti-Inflammatory Mediators on Locations of In-Stent Reocclusions in Elderly Patients - Xia Li; Dianxuan Guo; Ying Chen; Youdong Hu; Fenglin Zhang (Mediators of Inflammation)
Imbalances of proatherogenic inflammatory and antiatherogenic inflammatory mediators were involved in the pathogenesis of atherosclerosis. This study sought to investigate the effects of proatherogenic inflammatory and antiatherogenic inflammatory mediators on the proximal, middle, and distal coronary artery reocclusions in elderly patients after coronary stent implantations. We measured the expression levels of proatherogenic inflammatory/antiatherogenic inflammatory cytokines. This included interleukin-1 β (IL-1 β), interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α), high-sensitivity C-reactive protein (hs-CRP), interleukin-10 (IL-10), interleukin-17 (IL-17), interleukin-13 (IL-13), and interleukin-37 (IL-37) in the elderly patients with the proximal, middle, and distal coronary artery reocclusions after coronary stent implantations. Levels of IL-1 β, IL-6, IL-8, TNF-α, and hs-CRP were remarkably increased (P<0.001), and levels of IL-10, IL-17, IL-13, and IL-37 were remarkably lowered (P<0.001) in the elderly patients with the proximal, middle, and distal coronary artery reocclusions. Imbalances of proatherogenic inflammatory and antiatherogenic inflammatory mediators may be involved in the formation and progression of proximal, middle, and distal coronary artery reocclusions in elderly patients after coronary stent implantations.